Assessment of physicians' knowledge about brain death and organ donation and associated factors. Issue 38 (23rd September 2022) - Fernandes Vasconcelos, Tauana; Gonçalves Menegueti, Mayra; Corsi, Carlos Alexandre Curylofo; Michelon-Barbosa, Jéssyca; Sato, Lucas; Basile-Filho, Anibal; Becari, Christiane; Dantas, Rosana Aparecida Spadoti; Auxiliadora-Martins, Maria
Abstract : Precocity and assertiveness when diagnosing brain death are essential for identifying potential donors. To assess the knowledge of physicians about brain death and organ donation, cross-sectional web-based survey was carried out with physicians from different specialties. The knowledge about brain death and organ donation was assessed by a questionnaire with 12 multiple-choice or multiple-answer questions (possible range from 0 to 12). The nonparametric Mann–Whitney and Kruskal–Wallis tests were performed to verify the association between the physicians' knowledge and others variables. The project was approved by the Research Ethics Committee of the Hospital das Clínicas, Faculty of Medicine of Ribeirão Preto, University of São Paulo, under number 4.022.657, and all patients agreed to participate and provided free prior-informed consent. Three hundred sixty physicians were included in this study, most of them have postgraduate (55%) and 59.2% were intensive care physicians. The median of responses was 5 (obtained range from 0 to 10). The participants were classified in 2 groups: with satisfactory knowledge (scores above 5) or without satisfactory knowledge (scores equal/below 5). There was better performance among participants who: completed graduation between 6 and 10 years ( P  < .012); were intensive care physicians ( P  < .002); had participated in training courses ( P  < .001); and those who had worked in intensive care unit (ICU) from 6 to 10 years ( P  < .023); had performed over 10 brain death protocols ( P  < .001), and felt safe to talk to family members about brain death ( P  < .001). The results showed that the participants had low knowledge about diagnosis of brain death and organ donation protocols despite the majority working in ICUs. Be an intensive care physician, had large time experience in ICU, and had performed brain death protocols were associated with unsatisfactory knowledge concerning the subject.